An item development, content validity, and feasibility study towards the Indonesian recovery scale for patients with schizophrenia. Issue 11 (November 2022) - Saputra, Alvin; Kusumawardhani, A.A.A.A.; Elvira, Sylvia Detri; Wiguna, Tjhin
Abstract: Recovery of mental health in people with schizophrenia spectrum disorders is essential, thus it is very important to be assessed. One instrument that measures mental health recovery is the Recovery Assessment Scale – Domains and Stages (RAS-DS), developed within the Australian cultural context to facilitate mental health recovery. An instrument based on conceptions of mental health recovery in Indonesia is still needed. This qualitative study aimed to characterise how persons with schizophrenia spectrum disorders in Indonesia define mental health recovery, to develop the Skala Pemulihan Pasien Skizofrenia (SPPS)/Indonesian Recovery Scale for Patient with Schizophrenia (I-RSPS), and to determine the content validity of the I-RSPS. Qualitative data were collected through focus group discussions (n = 11); data were analysed using conventional content analysis and thematic analysis. An inductive approach was used to develop the I-RSPS items. Content validity was evaluated using an item-level content validity index (I-CVI) and a scale-level content validity index (S-CVI). Validity evaluation trials were conducted with ten participants. Perceptions of mental health recovery in people with schizophrenia spectrum disorders in Indonesia were investigated along social, existential, clinical, functional, and physical dimensions. Some perceptions of family, religion, and spirituality are unique to the Indonesian socio-cultural context, as are some stigmas I-RSPS consists of 40 items with good content validity, with an average I-CVI of 0.99 and an average S-CVI of 0.93, and it was rated as easy to use, with 5.4 min (range: 3–10 min) being the average duration required to complete the scale. Abstract : Schizophrenia; Schizophrenia spectrum disorders; Mental health recovery; Personal recovery.